Разработка новых схем резистивной защиты высоковольтных конденсаторов мощных емкостных накопителей энергии от аварийных токов - Баранов, Михаил Иванович; Рудаков, Сергей Валерьевич (НТУ "ХПИ", 2015)
Приведены результаты разработки новых схем резистивной защиты высоковольтных импульсных конденсаторов мощных емкостных накопителей энергии от разрушающего действия на них аварийных импульсных токов амплитудой до сотен килоампер, протекающих при отсутствии подобной защиты через данные конденсаторы при электрическом пробое их внутренней или наружной изоляции.

Purpose. Development of new charts of capacitance-resistance defense of high-voltage capacitors of powerful capacity stores of energy (CSE) from emergency large impulsive currents (LIC) at the electric hasp of one of condensers of such CSE on the stage of their charge or discharge. Methodology. Electrophysics bases of the technique of high-voltage and large pulsed currents, and also scientific and technical bases of planning of devices of high-voltage impulse technique. Results. Two new charts of capacitance-resistance defense of high-voltage impulsive capacitors are offered for powerful CSE of one- and multi-module execution from emergency LIC, being based on the use of high-voltage permanent graphite-ceramic resistors of type of TVO-60 a face value from 24 to 100 Ohm, set on the high-voltage conclusions of all of condensers of CSE. One of the developed capacitance-resistance charts of defense of condensers for powerful one-module CSE passed practical approbation. Originality. It is shown that application of the developed charts of capacitance-resistance defense of high-voltage condensers of powerful CSE is provided by frequent limitation of amplitude of emergency LIC, flowing through broken through an electric discharge condenser of CSE on the stage of his charge or discharge. Such limitation emergency LIC is prevented by explosion destruction of the damaged condenser of high-voltage CSE. Practical value. The use of the developed charts of capacitance-resistance defense of high-voltage capacitors from emergency LIC allows substantially to promote functional safety of powerful CSE of one- and multi-module execution and provide the safe terms of labour for a scientific and technical personnel, attendant similar CSE.
Development of new charts of capacitance-resistance defense of high-voltage capacitors of powerful capacity stores of energy from emergency currents
Keywords: резистор графито-керамический; мощность; устройство повысительно-выпрямительное; импульс; сопротивление; разряд; изоляция